Metastatic Syringocystadenocarcinoma Papilliferum: A Case Report, Tumor Genomic Profiling, and Literature Review - Erdem Altunel; Aleksandr Perepletchikov; Olga Kozyreva (Case Reports in Oncological Medicine)
Syringocystadenocarcinoma papilliferum (SCACP) is an extremely rare cutaneous neoplasm of the apocrine or eccrine sweat glands. Solid and cystic glandular structures with cribriform and tubular architecture along with CK5/6, pankeratin and p63 immuno-profile set apart SCACP from other cutaneous malignancies. Wide local excision (WLE) has been the mainstay treatment for localized SCACP; however, no standard treatment has yet been established for unresectable or metastatic disease. Herein, we report a 74-year-old male with SCACP, who initially presented with a painful nodule on the upper back and later developed metastatic disease. He was treated with carboplatin and paclitaxel with concurrent intensity-modulated radiation therapy (IMRT), which resulted in disease stabilization for 12 months. Next generation sequencing (NGS) revealed a total of 18 genomic alterations associated with potential benefit from targeted therapeutics. PD-L1 expression was identified in 70% of tumor cells. These findings suggest that the opportunity of targeted therapeutics and immunotherapy exist as for metastatic SCACP. Reporting molecular profile of the rare tumors with no established standard treatment options should be encouraged.